Voltammetric investigation of microbiological growth media and carbon nanotube modified electrodes : a case study of oxytetracycline - Kruid, Jan (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2013)
Oxytetracycline (OTC) is a broad spectrum antibiotic used extensively in the agricultural and human-health sector, and is effective against various gram positive and "“negative bacteria as well as large viruses and certain pathogenic Rickettsiae. This study addresses the lack of voltammetric knowledge regarding the electroanalytical characterisation of OTC and its analysis in complex matrices. Cyclic voltammetry (CV) revealed several irreversible anodic peaks for OTC at a bare glassy carbon electrode (GCE). These current responses were improved through the selection of a diluent for OTC stock preparation, electrolyte solution and electrolyte pH, stir time and applied preconditioning potential. Under enhanced adsorptive conditions and using square wave voltammetry (SWV), a detection limit of 24.3 nM was achieved. The electrode surface could be renewed in vitro for 10 successive scans. OTC oxidation was characterised as a one electron:one proton ECiE mechanisms. Next, investigating the viability of voltammetry in various complex microbiological growth media revealed that selected growth media contained interfering redox active components, which, while simultaneously coating the electrode surface, effectively reduced GCE performance and lowered the active electrode surface area, as ascertained through CV and electrochemical impedance spectroscopy (EIS) studies. This interference lowered OTC current response in the presence of growth media which was partially recovered by appropriate growth media selection and sample dilution. In testing the use of acid functionalised multi-walled carbon nanotubes (MWCNTs) to improve anodic OTC response, charge-based attraction was observed between the MWCNT dispersal agent NafionÂ® and OTC, while increased surface area associated with prolonged acid functionalisation time aided in improving OTC current response.
Keywords: Voltammetry; Electrodes; Oxytetracycline; Carbon nanotubes